A study on willingness and influencing factors to receive COVID-19 vaccination among Qingdao residents - Feng Yang; Xiaofan Li; Xiaoting Su; Tingting Xiao; Yang Wang; Ping Hu; Han Li; Jing Guan; Haizhen Tian; Peng Wang; Wencheng Wang (Taylor & Francis Group, 2021)
This study investigated the willingness of Qingdao residents to receive COVID-19 vaccination in 2020 and any factors that might influence them. All data were collected by telephone questionnaires and were utilized for analyzing the potential factors of willingness to be vaccinated through descriptive analysis and logistic regression analysis. Of the 2,802 respondents, 2,284 (81.5%) said they would agree to receive the vaccine against COVID-19. People who earned high incomes, who carefully followed media news on COVID-19 vaccine, who looked forward to successful vaccine research, and who closely followed vaccine protective efficacy expressed more interest in being vaccinated than other people did. In addition, people who paid attention to protective efficacy of vaccine, vaccine price, and expert opinion were more likely to accept COVID-19 vaccination than people who focused on vaccine safety. When vaccine price was ≥201 RMB, people were less likely to accept vaccination than ≤200 RMB. 1,842 respondents (65.7%) wished that government could provide COVID-19 vaccination for free. This study suggests that the government should increase vaccination compliance by strengthening publicity efforts and decreasing vaccine price.